Vernacular buildings and urban social practice : wood and people in early modern Swedish society - Nilsen, Andrine, (Archaeopress Archaeology, 2021)
Wooden buildings housed the majority of Swedish urban populations during the early modern era, but many of these buildings have disappeared as the result of fire, demolition, and modernisation. This book reveals the fundamental role played by the wooden house in the formation of urban Sweden and Swedish history.